Patient’s expectation of orthodontic treatment attending tertiary care dental hospital in Kathmandu - Shrestha, Bikash Veer; Piya, Anshu; Khapung, Anju; Bhattarai, Prakash (Orthodontic Journal of Nepal, 2021)
Introduction: Understanding of patient’s expectation and attitude towards orthodontic treatment plays an important role towards a successful treatment outcome and behavioral management. Materials and Method: All the patients (270) attending department of Orthodontics in Nepal Medical College for the first time were included in the study. The descriptive study is done. A structured questionnaire was used to obtain the socio-demographic information and responses to questions on their expectation of orthodontic treatment. Results: Majority of the respondents had higher expectations on aesthetic outcome of orthodontic treatment than the functional outcomes. They expected to have better smile, teeth straightened and have confidence socially. The lowest mean scores were obtained in the domains of improvement in career and making speech easier. Females had significant higher scores than male participants in all domains explored with the mean highest score in the domain of better smiles; while the highest male mean score was in the domain of straightened teeth. Conclusion: To achieve successful orthodontic treatment result, patient cooperation is necessary. Agreeing with the patient on realistic expected treatment outcomes by the orthodontist before the treatment is required so that they are not disappointed with the final appearance.